2020
DOI: 10.1080/23744235.2020.1794027
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis relapse is more common than reinfection in Beijing, China

Abstract: Background: Recurrent tuberculosis (TB) is a major health problem in countries with a high TB burden. It is very necessary to elucidate the situation of recurrent TB in Beijing, capital of China. Objective: To determine the proportion of recurrent tuberculosis (TB) cases and to identify relapsed or reinfected cases, as well as risk factors associated with recurrence in Beijing. Methods: We conducted a retrospective study that included all TB cases in Beijing that were successfully treated from 2013 to 2015. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The results of this retrospective study found that the recurrence rate after successful treatment was lower than that reported in areas with high TB incidence [7]. Yi Liu et al reported a TB recurrence rate of 6.8% (275/4,043) in Beijing, China, with a 3-year follow-up period from 2013 to 2015 [8]. Additionally, Suzanne Verver et al reported a 14% (61/447) recurrence rate after successful treatment, with a 5-year follow-up period in Cape Town, South Africa [9].…”
Section: Discussionmentioning
confidence: 85%
“…The results of this retrospective study found that the recurrence rate after successful treatment was lower than that reported in areas with high TB incidence [7]. Yi Liu et al reported a TB recurrence rate of 6.8% (275/4,043) in Beijing, China, with a 3-year follow-up period from 2013 to 2015 [8]. Additionally, Suzanne Verver et al reported a 14% (61/447) recurrence rate after successful treatment, with a 5-year follow-up period in Cape Town, South Africa [9].…”
Section: Discussionmentioning
confidence: 85%
“…[18][19][20][21] Previous studies reported that 58.2-69.0% of recurrent TB in China were resulted from relapse of the original M. tuberculosis strain rather than from reinfection with a new strain. [22][23] However, we are not able to comment on this as we did not test those who represented with TB to establish if it was relapse or reinfection. As relapse usually occurs because of inadequate treatment, 5 and may reflect the quality of program for certain treatment regimens and TB programs need to pay attention to recurrence rates in those people cured or successfully completing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemics data were obtained and aggregated from the Collection of Meteorological Records in China over the Past Three Thousands Years (Zhang, 2004), Historical Records of Infectious Diseases in China (Li, 2004), and Epidemic Records in Historical China (Zhang, 2007). The three datasets are tabulated from official dynastic histories and local chronicles.…”
Section: Methodsmentioning
confidence: 99%